Sperm ultrastructure of shrimps from the family Penaeidae (Crustacea: Dendrobranchiata) in a phylogenetic context - Camargo, Tavani Rocha [UNESP]; Rossi, Natalia; Castilho, Antonio L. [UNESP]; Costa, Rogério C. [UNESP]; Mantelatto, Fernando L.; Zara, Fernando José [UNESP] (Elsevier, 2017)
We describe the sperm ultrastructure of six penaeid species, including at least one member of each tribe (Penaeini, Parapenaeini and Trachypenaeini). Fragments of the vas deferens of the Penaeidae Farfantepenaeus brasiliensis, Farfantepenaeus paulensis, Litopenaeus schmitti, Parapenaeus americanus, Rimapenaeus constrictus and Xiphopenaeus kroyeri were fixed and processed according to the routine for transmission electron microscopy. The morphological results were contextualized in an evolutionary perspective using molecular markers for the phylogenetic reconstruction of this group. A phylogram was proposed by Bayesian inference based on 1007 bp of 33 sequences of the combined genes (16S rDNA and COI mtDNA) from 27 dendrobranchiate specimens. Our findings show that morphological differences in the sperm ultrastructures of members among the tribes of Penaeidae can be used as a baseline to understand their evolutionary relationships. Individuals from the Penaeini tribe show plesiomorphic characteristics in the sperm ultrastructure compared to the Trachypenaeini tribe from which they were derived, such as shrimp from family Sicyoniidae. The morphological complexity of the sperm of the different penaeid members corroborated with the genetic phylogeny, which showed different clades for each tribe and the close relationship with Sicyoniidae. The sperm features of the selected species studied here reflected their evolutionary history. These features confirm the previous phylogenetic hypothesis and question the monophyly of Penaeidae, which should be verified in the future with a more complete set of representative members of each tribe.
Keywords: Bayesian inference; Decapoda; Molecular phylogeny; Sperm ultrastructure; Transmission electron microscopy